Mobile Learning Menggunakan Metode Pengendalian Bahan Ajar (Studi Kasus : Mata Kuliah Sistem Operasi) - Indra Listiawan; Zaidir Zaidir (Institut Teknologi Dirgantara Adisutjipto, 2018)
Starts with the development of e-learning with simple technology to social network based on technology such as Edmudo. Because mobile phone users are very large more than two times the internet users, then some experts try to develop a model of learning with mobile phones.The problem is how to give a strong motivation for students to want to use mobile technology in teaching and learning process. This proposed research will create a mobile learning application combined with the control of teaching materials with the aim to increase student enthusiasm to obtain advanced materials after completing the existing material.Outcome to be achieved from this research is the contribution of research in the form of carelearning application with teaching material control method. This study focuses more on the side of instructional media or applications than with the content. Further research involving what form of content appeals to students still needs to be done as a future work of this research.